# Negated Fibonacci and the floor function

• Let $$F_n$$ be A000045 (i.e., Fibonacci numbers). Here

$$F_n = F_{n-1} + F_{n-2}, \\ F_0 = 0, F_1 = 1, \\ F_{-n} = (-1)^{n-1}F_n$$

I conjecture that

$$F_{-n} = \left\lfloor\frac{n+1}{2}\right\rfloor - \sum\limits_{i=1}^{n-1} \left(\left\lfloor\frac{n-i+1}{2}\right\rfloor + 1\right)F_{-i}, \\ F_{-n} = \left\lfloor\frac{2(n+1)}{3}\right\rfloor - \sum\limits_{i=1}^{n-1} \left(2\left\lfloor\frac{n-i+2}{3}\right\rfloor + 1\right)F_{-i}$$

Here is the PARI/GP program to check it numerically:

test1(n) = fibonacci(-n) == ((n+1)\2 - sum(i=1, n-1, ((n - i + 1)\2 + 1)*fibonacci(-i)))
test2(n) = fibonacci(-n) == (2*(n+1)\3 - sum(i=1, n-1, (2*((n - i + 2)\3) + 1)*fibonacci(-i)))


Is there a way to prove it? Is there any other similar formulas?

We have $$F_{-n}=\frac{(-a_-)^n-(-a_+)^n}{\sqrt5} \tag{1}\label{1}$$ with $$a_\pm:=\frac{1\pm\sqrt5}2.$$

We also have the easy formula for $$\sum_{j=j_1}^{j_2}(p+qj)x^j$$, which yields
$$\sum_{i=1}^{n-1} \left(\left\lfloor\frac{n-i+1}{2}\right\rfloor + 1\right)u^i \\ =-\frac{(u-1) u^2 \left\lfloor \frac{n+1}{2}\right\rfloor +(u-1) u \left\lfloor \frac{n}{2}\right\rfloor -2 u^{n+2}+u^n+u^3+u^2-u}{(u-1)^2 (u+1)}. \tag{2}\label{2}$$

Your first identity easily follows from \eqref{1} and \eqref{2}.

Other such identities should be derivable quite similarly.

As a complement to Iosif's answer, I'll give the inductive proof. First, some preliminaries: note that by recursively applying the defining relations, $$F_n=F_{n-1}+F_{n-3}+...+F_2+1=1-(F_{-(n-1)}+F_{-(n-3)}+...+F_{-2}),\text{ when }n\text{ is odd,}$$ and $$F_n=F_{n-1}+F_{n-3}+...+F_1=F_{-(n-1)}+F_{-(n-3)}+...+F_{-1},\text{ when }n\text{ is even.}$$ Therefore, $$F_{-1}+F_{-2}+...+F_{-(n-1)}=1+(-1)^{n-1}F_{n-1}+(-1)^{n}F_{n} \\ =1-F_{-(n-1)}-F_{-n}. \tag{1}\label{eq:1}$$

Now, we start the inductive proof of your first statement. Clearly it holds for $$n=1,2$$.

Suppose that $$n>2$$ is odd. By equation \eqref{eq:1} and the inductive hypothesis, we obtain $$\begin{eqnarray*} F_{-n} &=& F_{-(n-2)} + \left(1-2F_{-(n-1)}-2F_{-(n-2)}-\sum_{i=1}^{n-3}F_{-i}\right)\\ &=&\left(\left\lfloor \frac{n-1}{2} \right\rfloor - \sum_{i=1}^{n-3}\left( \left\lfloor \frac{n-i-1}{2}\right\rfloor +1 \right)F_{-i}\right) + ... \\ &&\text{ ...} +\left(1-2F_{-(n-1)}-2F_{-(n-2)}-\sum_{i=1}^{n-3}F_{-i}\right) \\ &=&\left\lfloor \frac{n+1}{2} \right\rfloor - \sum_{i=1}^{n-1}\left( \left\lfloor \frac{n-i+1}{2}\right\rfloor +1 \right)F_{-i} \end{eqnarray*}$$ as required. The cases of $$n$$ even, and the second of your formulae, are similar.